Medical Student Abuse During Clinical Clerkships in Japan - Nagata-Kobayashi, Shizuko (Blackwell Science Inc, 2006)
OBJECTIVE: To assess the prevalence of medical student abuse during clinical clerkships in Japan. DESIGN: A cross-sectional questionnaire survey. SETTING: Six medical schools in Japan. PARTICIPANTS: Final year (sixth-year) and fifth-year medical students in the period from September 2003 to January 2004. From a total of 559 students solicited, 304 (54.4%) returned the questionnaire, and 276 (49.4%: 178 male and 98 female) completed it. MEASUREMENTS: Prevalence of medical student abuse in 5 categories: verbal abuse, physical abuse, academic abuse, sexual harassment, and gender discrimination; differences in abusive experience between male and female students; types of alleged abusers; reporting abusive experiences to authorities; and emotional effects of abusive experiences. RESULTS: Medical student abuse was reported by 68.5% of the respondents. Verbal abuse was the most frequently experienced abuse (male students 52.8%, female students 63.3%). Sexual harassment was experienced significantly more often (P<.001) by female students (54.1%) than by male students (14.6%). Faculty members were most often reported as abusers (45.2% of cases). Abuse occurred most frequently during surgical rotations (42.0% of cases), followed by internal medicine (25.1%) and anesthesia rotations (21.8%). Very few abused students reported their abusive experiences to authorities (8.5%). The most frequent emotional response to abuse was anger (27.1% of cases). CONCLUSIONS: Although experience of abuse during clinical clerkships is common among medical students in Japan, the concept of “medical student abuse” is not yet familiar to Japanese. To improve the learning environment, medical educators need to take action to resolve this serious issue.